Identification and Evaluation of Antioxidant and Anti-Aging Peptide Fractions from Enzymatically Hydrolyzed Proteins of Spirulina platensis and Chlorella vulgaris - Baran Masoumifeshani; Abdolmohammad Abedian Kenari; Ignacio Sottorff; Max Crüsemann; Jamshid Amiri Moghaddam (Marine Drugs)
Microalgae are a promising source of bioactive compounds, particularly proteins and peptides, with potential applications in skin health and the cosmetic industry. This study investigated the antioxidant and anti-aging properties of peptide fractions derived from Spirulina platensis and Chlorella vulgaris. Both microalgae were cultivated, and their proteins were subsequently extracted, enzymatically hydrolyzed with alcalase, and fractionated through ultrafiltration. Alkaline extraction yielded 82% protein from S. platensis and 72% from C. vulgaris. Enzymatic hydrolysis predominantly yielded <3 kDa peptides, which exhibited strong antioxidant activity reaching 78% for 2,2-diphenyl-1-picrylhidrazol (DPPH), 82% for 2,2′-azinobis-3-etilbenzothiazoline-6-sulfonic acid (ABTS), and 74% for ferric reducing antioxidant power (FRAP), with IC50 values as low as 23.44 µg/mL for ABTS inhibition in C. vulgaris. These peptides also significantly inhibited skin-aging enzymes, showing 84% inhibition of elastase, 90% of collagenase, and 66% of tyrosinase. Mass spectrometry and GNPS molecular networking of the <3 kDa fraction identified several di- and tri-peptides, including Lys-Val, Val-Arg, His-Ile, Lys-Leu, Ile-Leu, and Leu-Phe, Tyr-Phe, and Leu-Gly-Leu, potentially contributing to these bioactivities. These findings suggest that the enzymatic hydrolysis of S. platensis and C. vulgaris proteins provides a sustainable and natural source of bioactive peptides for antioxidant and anti-aging applications in food, pharmaceutical, and cosmetic industries.